The Influence of Environmental Knowledge and Environmental Concern on Consumers' Purchase Intention Toward Sustainably Packaged Products - Jihan Handayani; Aida Sari (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
The purpose of this study is to investigate how consumers' purchase intentions for items with sustainable packaging are impacted by environmental awareness and concern. The study uses a survey method and a quantitative methodology. Information was gathered from 120 Alfamart customers in Bandar Lampung, Indonesia, who had previously bought goods using environmentally friendly packaging. Multiple linear regression was used to examine the data and determine how the variables related to one another. The findings demonstrate that purchasing intention is positively and significantly impacted by both environmental knowledge and environmental concern. Environmental concern has a greater impact than environmental knowledge among the two factors. These results suggest that customers' intentions to buy environmentally friendly products are influenced by both affective and cognitive variables. Customers are more likely to buy products with sustainable packaging if they have a greater awareness of environmental issues and a greater concern for environmental sustainability. This study adds to the body of knowledge on green consumer behavior, especially as it relates to retail customers in developing nations. It also offers useful recommendations for governments and merchants looking to encourage sustainable purchase.